Comparison of the Structure and Diversity of Root-Associated and Soil Microbial Communities Between Acacia Plantations and Native Tropical Mountain Forests - Sawada, Kozue; Watanabe, Shinichi; Nguyen, Ho Lam; Sugihara, Soh; Seki, Mayuko; Kobayashi, Hana; Toyota, Koki; Funakawa, Shinya (Frontiers in Microbiology, 2021)
Deforestation of native tropical forests has occurred extensively over several decades. The plantation of fast-growing trees, such as Acacia spp., is expanding rapidly in tropical regions, which can contribute to conserve remaining native tropical forests. To better understand belowground biogeochemical cycles and the sustainable productivity of acacia plantations, we assessed the effects of vegetation (acacia plantations vs native forests) and soil types (Oxisols vs Ultisols) on soil properties, including the diversity and community structures of bacteria and fungi colonizing surface and subsurface roots and soil in the Central Highlands of Vietnam. The results in surface soil showed that pH was significantly higher in Acacia than in Native for Oxisols but not for Ultisols, while exchangeable Al was significantly lower in Acacia than in Native for Ultisols but not for Oxisols. Bacterial alpha diversity (especially within phylum Chloroflexi) was higher in Acacia than in Native only for Oxisols but not for Ultisols. These results suggest that soil pH but not exchangeable Al can be the critical factor to determine bacterial diversity. Acacia tree roots supported greater proportions of copiotrophic bacteria, which may support lower contents of soil inorganic N, compared to native tree roots for both Oxisols and Ultisols. Acacia tree roots also supported greater proportions of plant pathogenic Mycoleptodiscus sp. but appeared to reduce the abundances and diversity of beneficial ECM fungi compared to native tree roots regardless of soil types. Such changes in fungal community structures may threaten the sustainable productivity of acacia plantations in the future.